FILSAFAT MANUSIA DALAM PEMIKIRAN THOMAS HOBBES DAN RELEVANSINYA DENGAN PENGEMBANGAN KONSEP HAK ASASI MANUSIA (HAM) DI INDONESIA - , Mashudi, Dr. Misnal Munir ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The title of this study Human Philosophy According to Thomas Hobbes and Its Relevance to the development concept of Human Rights in Indonesia. Indonesian nation is in the midst of globalization are completely open perceived vulnerability still contain conflict, should be keeping the state of nature that have been submitted to the government. Governments in carrying out their duties can not be separated from the role of the community. The relationship between government and society regulated by law made by mutual agreement which has a strong holding capacity in regulating human behavior, in order to create reconciliation together who had aspired to the Indonesian nation. To keep the reconciliation together, the Indonesian people have a natural formulation of the concept of rights in the context of human rights. The purpose of this study is to explore the meaning state of nature in thinking Thomas Hobbes and suggests its relevance with the development of Human Rights in Indonesia. This research is a kind of library research. Material object in this study is the concept of natural rights in the work of Thomas Hobbes Leviathan. This study uses a formal object approach to human philosophy. Method in this researcher is a hermeneutics method, including the interpretation and Verstehen. Research also use heuristics method, used to analyze state of nature in Thomas Hobbes thought that can be found relevance to the development of Human Rights in Indonesia. The results in this study were human being, according to Hobbes can guarantee reconciliation together if willing to make a social contract to abolish absolute natural right given to one ruler or government. Attitude of the government is using power and other means that it deems appropriate, for the sake of reconciliation together. Feature of the social contract that contains three meanings: First, an agreement among the individuals to end the state of nature and form of civil society. Second, the social contract is done by individuals who are naturally isolated and anti-social. Third, the unity of the people who shaped by the social contract is more a consequence of sovereignty rather than the source of sovereignty. Starting from here, Thomas Hobbes that ideas of natural rights for the development of human rights in Indonesia, seen on a security order and peace among the people by the people in general and the government and the people in particular. It is the purpose of the \"social contract\" that aspired of nations. According to the principles of social contract that any rights of the people with his own will leaded and forth for the government's obligations. Likewise, the constitutional authority owned by the government also leaded and forth with the constitutional obligations that must be complied with and fulfilled by the people.